New Epidermal-Growth-Factor-Related Insights Into the Pathogenesis of Multiple Sclerosis: Is It Also Epistemology? - Scalabrino, Giuseppe (Frontiers in Neurology, 2021)
Recent findings showing that epidermal growth factor (EGF) is significantly decreased in the cerebrospinal fluid (CSF) and spinal cord (SC) of living or deceased multiple sclerosis (MS) patients, and that its repeated administration to rodents with chemically- or virally-induced demyelination of the central nervous system (CNS) or experimental allergic encephalomyelitis (EAE) prevents demyelination and inflammatory reactions in the CNS, have led to a critical reassessment of the MS pathogenesis, partly because EGF is considered to have little or no role in immunology. EGF is the only myelinotrophic factor that has been tested in the CSF and spinal cord of MS patients, and it has been shown there is a good correspondence between liquid and tissue levels. This review: (a) briefly summarises the positive EGF effects on neural stem cells, oligodendrocyte cell lineage, and astrocytes in order to explain, at least in part, the biological basis of the myelin loss and remyelination failure in MS; and (b) after a short analysis of the evolution of the principle of cause-effect in the history of Western philosophy, highlights the lack of any experimental immune-, toxin-, or virus-mediated model that precisely reproduces the histopathological features and “clinical” symptoms of MS, thus underlining the inapplicability of Claude Bernard's crucial sequence of “observation, hypothesis, and hypothesis testing.” This is followed by a discussion of most of the putative non-immunologically-linked points of MS pathogenesis (abnormalities in myelinotrophic factor CSF levels, oligodendrocytes (ODCs), astrocytes, extracellular matrix, and epigenetics) on the basis of Popper's falsification principle, and the suggestion that autoimmunity and phologosis reactions (surely the most devasting consequences of the disease) are probably the last links in a chain of events that trigger the reactions. As it is likely that there is a lack of other myelinotrophic growth factors because myelinogenesis is controlled by various CNS and extra-CNS growth factors and other molecules within and outside ODCs, further studies are needed to investigate the role of non-immunological molecules at the time of the onset of the disease. In the words of Galilei, the human mind should be prepared to understand what nature has created.